Internet addiction: clinical aspects and treatment strategies - Öztürk, Özgür; Odabaşıoğlu, Gürkan; Eraslan, Defne; Genç, Yasin; Kalyoncu, Ö. Ayhan (Journal of Dependence, 2007)
Advances in technology and communication bring new risks while increasing life quality. Internet usage and computer skills have been unavoidable necessities in this so called ‘ technology era’. Beginning from mid 90’s, internet addiction began to attract the attention of clinicians with the increasing number of patients applying with variety of symptoms like: unlimited internet usage despite academical and social failures and feeling excessive anxiety when internet acces is not possible. Although first cases were from developped western countries, recently many cases from other countries have began to be recognized in literature pointing out that rapid increase in the amount of people who have internet access all over the world also accelerates the abuse and addiction of internet at the same time. This new addiction type is especially a risk factor for 12-18 years old adolescent group. Remembering the dense youth population in our country, this addiction must be well identified and recognized by clinicians working with addiction.
Keywords: Internet addiction; hyperactivity; dopaminergic reward systems